Building a mathematical model for the free groundwater Resources of the plain area in the lattakia basin - Rajab, Nedaa Saedallah; Mohammed, Ahmed; Hayek, Sharif (Journal of natural sciences, life and applied sciences, 2021)
The results of the stratigraphic modeling of the study area showed that the stratigraphic formations constitute a hydrogeological system that is hydrodynamically linked to each other represented by a water layer with a free underground flow. The results of the mathematical model that was built for the region also showed that the high values of the leaching factor were concentrated in the northern and central part of the research area, where the faults were located, the difference between the input values and the calibration results in most areas of the hydraulic conductivity distribution of the layer did not exceed 10%. The water resources in the northeastern part of the study area are of good quality, large quantities, and easy to invest, with a total intake of (134607.3) m3/day. The thickness of the carrier ranged about 50 m in the northern section and increased towards the area of the falcon band within the course of the Arab River to reach about 125 m. As for the thickness of the carrier in the southern section, it ranged between (75 – 60) m. the groundwater system in the study area is stable, and the largest part of the amount of water resources formed in the region to the lateral inflow of the ground and and amounted to about 90% of total value of the resources.